Electronic Audit in Auditing Financial Statements of Local Governments - Muhammad Daud (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
This research aims to determine how far the implementation of electronic audit (e-audit) on auditing local government financial statements by Audit Board of the Republic of Indonesia representative of the Special Region of Yogyakarta (BPK DIY) can go and the benefits of e-audit for auditees to report their financial management accountability. An interpretive qualitative approach with a case study method was used in this research. The primary data were obtained directly through interview with 2 BPK auditors who has been examined the financial statements of the DIY Government and 4 auditees; head of Dinas Pengelolaan Pendapatan, Keuangan dan Aset (DPPKA) Special Region of Yogyakarta, Sleman Regency, Yogyakarta City, and Gunungkidul Regency. The secondary data that used to support the results are the BPK Performance Accountability Reports in 2015, and Laporan Kinerja Instansi Pemerintah (LAKIP) of Special Region of Yogyakarta in 2015. The implementation of e-audit succeeded in improving the performance of local government financial statement audits, especially in audit implementation stage, such as collection and analysis of audit evidences by auditors so that the process of auditing financial statements became more effective and efficient. However, the e-audit has not succeeded to meet up the needs of auditee to access the BPK audit reports. This research only focused on the stages of audit implementation so that further research can be developed in the use of e-audit for audit planning and reporting.